2019
DOI: 10.1073/pnas.1902058116
|View full text |Cite
|
Sign up to set email alerts
|

Social media’s enduring effect on adolescent life satisfaction

Abstract: In this study, we used large-scale representative panel data to disentangle the between-person and within-person relations linking adolescent social media use and well-being. We found that social media use is not, in and of itself, a strong predictor of life satisfaction across the adolescent population. Instead, social media effects are nuanced, small at best, reciprocal over time, gender specific, and contingent on analytic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
275
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(332 citation statements)
references
References 11 publications
30
275
2
1
Order By: Relevance
“…separations. Yet, some have argued that using social medial only exacerbates subjective feelings of isolation(118, for review) but see (119,120). Future studies could compare SN/VTA responses to social cues following isolation with and without access to social media.…”
Section: Discussionmentioning
confidence: 99%
“…separations. Yet, some have argued that using social medial only exacerbates subjective feelings of isolation(118, for review) but see (119,120). Future studies could compare SN/VTA responses to social cues following isolation with and without access to social media.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, research has shown that social media use alone is not a predictor of loneliness as other factors have to be considered (Cigna 2018;Kim et al 2009). In fact, while some research has shown no effect of social media on wellbeing (Orben et al 2019), other research has shown that social media can benefit individuals through a number of different avenues such as teaching and developing socialization skills, allowing greater communication and access to a greater wealth of resources, and helping with connection and belonging (American Psychological Association 2011; Baker and Algorta 2016;Marker et al 2018). As well, a working paper by Crolic et al (2019) argues that much of the evidence of social media use on consumer well-being is of questionable quality (e.g., small and non-representative samples, reliance on self-reported social media use), and show that some types of social media use are positively associated with psychological well-being over time.…”
Section: Combatting Loneliness and Isolationmentioning
confidence: 98%
“…However, most of this evidence suffers from issues related to reverse causality (Cheng, Burke and Davis (2019)) and inaccurate measures of self-reported social media use (Orben, Dienlin and Przybylski (2019)). Rigorous causal evidence on long term impacts of social media use on well-being is lacking.…”
Section: Introductionmentioning
confidence: 99%